Favorable outcome of immunotherapy in a rare subtype of hepatocellular carcinoma: a case report and literature review - Archwamety, Anita; Kunapinun, Nique; Sirinvaravong, Sirinart; Apisarnthanarak, Piyaporn; Akewanlop, Charuwan; Korphaisarn, Krittiya (Frontiers in Oncology, 2024)
Scirrhous hepatocellular carcinoma (S-HCC) represents an uncommon subtype of HCC. During radiological evaluation this unique subtype is frequently mistaken as cholangiocarcinoma, fibrolamellar HCC, or metastatic adenocarcinoma. Here, we present the case of a 50-year-old woman with a large hepatic mass. A triple-phase computed tomography of the liver revealed an arterial enhancing lesion without portovenous washout at hepatic segment 4a/8. The liver biopsy showed hepatocellular characteristics and was positive for Hep Par 1, CK7, CK19, Arginase 1 and CEA, indicating atypical S-HCC. This patient had achieved tumor control with combined treatment with atezolizumab plus bevacizumab and was then treated with lenvatinib after tumor progression. The patient died 15 months after the initial diagnosis.